The Kalpika Natha Mascot Dance: A Substance of Anthropological, Semiotic, and Aesthetic Studies - I Gusti Ayu Mas Nari Wulan; I Wayan Karja (Journal of Aesthetics, Creativity and Art Management, 2023)
The creation of a mascot dance entitled Kalpika Natha at SMP Negeri 2 Abiansemal is one of the ideas to create a symbol or identity through performing arts including dance, vocal art, and karawitan. In this interdisciplinary research, anthropological, semiotic, and aesthetic approaches are used. In anthropological studies, the art of mascot dance can be studied from the point of view of cultural and social aspects. The Kalpika Natha Mascot Dance as a representation of organizational identity can be a reflection of societal values and norms. Apart from that, the Kalpika Natha Mascot Dance can also be a medium to introduce and promote the culture of a region or country. Semiotic studies can assist in understanding the meaning and symbols contained therein which are interpreted through semiotic analysis to reveal the message the choreographer wants to convey. Furthermore, in the study of aesthetics, it can be seen from the form, the weight of the content of the Kalpika Natha dance. In this research, interdisciplinary studies of anthropology, semiotics, and aesthetics can provide a more comprehensive understanding of mascot dance as a form of performing art and promotional media. Thus, this research can provide broader implications for the development of the Kalpika Natha Dance in the future.